IT-BASED MEDIA IMPLEMENTATION MENTORSHIP IN LOEI PROVINCE PRIMARY SCHOOLS THAILAND - Paulina, Paulina; Muhammad, Ribeh Najib (Journal of English Teaching, Literature, and Applied Linguistics, 2020)
This community service activity stems from the lack of use of technology in the use of teaching media in several schools in Loei Province, Thailand. Educators tend to apply conventional media which ultimately gives the effect of boredom and decreased motivation to students. The role of teaching media is very important in the learning process of students, especially at the elementary school level where students tend to be active in moving and get bored quickly. Pre-surveys and interviews with schools and teachers that have been conducted show that students are more interested in learning activities by using technology-based teaching media. The use of technology or IT is not optimal in schools even though the school has been equipped with technological facilities such as laptops, computers, projectors and projector screens. The support from the principal and guardians of students for mastery of technology in teaching is very large, but due to the lack of information and knowledge about technology such as the application of teaching media, conventional techniques are always applied in every lesson. Armed with this problem, the service team offers a solution for assisting the creation of information and technology-based teaching media for English teachers in Loei Province, Thailand through several stages, namely 1. Introduction and strengthening of materials through socialization; 2. Assistance in making teaching media; 3. Monitoring of Media Implementation. The outputs that will be produced from this program are scientific publications in national journals with an unaccredited ISSN, publications in print and online mass media, increasing competitiveness (improvement of quality), and improving community values ​​(education). The additional outputs of this service activity are scientific publications in international journals, CD ROMs and tutorial books with ISSBN.